Striatal Chloride Dysregulation and Impaired GABAergic Signaling Due to Cation-Chloride Cotransporter Dysfunction in Huntington’s Disease - Serranilla, Melissa; Woodin, Melanie A. (Frontiers in Cellular Neuroscience, 2022)
Intracellular chloride (Cl–) levels in mature neurons must be tightly regulated for the maintenance of fast synaptic inhibition. In the mature central nervous system (CNS), synaptic inhibition is primarily mediated by gamma-amino butyric acid (GABA), which binds to Cl– permeable GABAA receptors (GABAARs). The intracellular Cl– concentration is primarily maintained by the antagonistic actions of two cation-chloride cotransporters (CCCs): Cl–-importing Na+-K+-Cl– co-transporter-1 (NKCC1) and Cl– -exporting K+-Cl– co-transporter-2 (KCC2). In mature neurons in the healthy brain, KCC2 expression is higher than NKCC1, leading to lower levels of intracellular Cl–, and Cl– influx upon GABAAR activation. However, in neurons of the immature brain or in neurological disorders such as epilepsy and traumatic brain injury, impaired KCC2 function and/or enhanced NKCC1 expression lead to intracellular Cl– accumulation and GABA-mediated excitation. In Huntington’s disease (HD), KCC2- and NKCC1-mediated Cl–-regulation are also altered, which leads to GABA-mediated excitation and contributes to the development of cognitive and motor impairments. This review summarizes the role of Cl– (dys)regulation in the healthy and HD brain, with a focus on the basal ganglia (BG) circuitry and CCCs as potential therapeutic targets in the treatment of HD.